Search for a Higgs boson decaying to two W bosons at CDF. - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
We present a search for a Higgs boson decaying to two W bosons in pp[over ] collisions at sqrt[s]=1.96 TeV center-of-mass energy. The data sample corresponds to an integrated luminosity of 3.0 fb;(-1) collected with the CDF II detector. We find no evidence for production of a Higgs boson with mass between 110 and 200 GeV/c;(2), and determine upper limits on the production cross section. For the mass of 160 GeV/c;(2), where the analysis is most sensitive, the observed (expected) limit is 0.7 pb (0.9 pb) at 95% Bayesian credibility level which is 1.7 (2.2) times the standard model cross section.